Narratives of secularism - Choueiri, Youssef M., 1948- author.
1 online resource.
Keywords: "This book offers a new interpretation of the rich narratives of Arab secularism contending that secularism as a set of ideas and a social movement is destined to loom large on the political and legal horizon of most Arab states. Youssef M. Choueiri provides a study of three moments in the development of secularism in the Arab World, the Machiavellian, the Alfierian and the Gramscian. It is within such a scope that secularism in its interaction with state-building projects, women's emancipation and religion is treated as an intellectual current and a discursive entity embedded in the political process of its diverse societies. Through the chapters Choueiri demonstrates how secularism occupies a pivotal presence in the religious and political life of the Arab world, exploring such interrelated configurations as indigenous contributions, diverse reforms and the impact of Western states. He concludes that secularism has become a moral prerequisite and a required vehicle in creating the necessary conditions for the success of democracy in the Middle East. Narratives of Secularism tackles the complexity and contemporary ramifications of the subject in a way that no previous single study has been able to. It will be relevant to both students and academics dealing with topics related to the Middle East including religion, politics, anthropology, and history"--